Marketing Strategy In PT. Raflesia Ocean Logistics Bengkulu City - Eddlyn Jervis; Sulisti Afriani; Eska Prima Monique Damarsiwi (Penerbit Jurnal Indonesia, 2021)
This research aims to find out marketing strategy at PT. Raflesia Ocean Logistics City of Bengkulu. This research was conducted using SWOT analysis method (Strength, Weakness, Opportunity, Threats). SWOT analysis is the identification of various factors systematically to formulate the right strategy for a company. From the results of the research shows the strength (Strenght) owned by PT. Raflesia Ocean Logistics Bengkulu city is 23.29. While weakness (Weaknesses) 10.55, so quadrant Internal Factor Analysis Strategy (IFAS) is 23.29-10.55 = 12.74. Opportunities of the strategy are 24.87, for threats as much as 13.57, so the quadrant of EFAS (Exsternal Factor Analysis Strategy) is 24.87-13.57=11.12 so that the position is in quadrant I in the SWOT analysis diagram. Companies should implement strategies that can support aggressive growth policies such as maintaining services and company performance, improving the quality of human resources by providing job training, and expanding the market such as adding cooperation links with planning new targets.